Development of a Working Hovercraft Model - S. H., Mohamed Noor; K., Syam; Abdul Aziz, Jaafar; M. F., Mohamad Sharif; Mohd Riduwan, Ghazali; Wan Ismail, Ibrahim; M. F., Atan (IOP Publishing, 2016)
This paper presents the development process to fabricate a working hovercraft model. The purpose of this study is to design and investigate of a fully functional hovercraft, based on the studies that had been done. The different designs of hovercraft model had been made and tested but only one of the models is presented in this paper. In this thesis, the weight, the thrust, the lift and the drag force of the model had been measured and the electrical and mechanical parts are also presented. The processing unit of this model is Arduino Uno by using the PSP2 (Playstation 2) as the controller. Since our prototype should be functioning on all kind of earth surface, our model also had been tested in different floor condition. They include water, grass, cement and tile. The Speed of the model is measured in every case as the respond variable, Current (I) as the manipulated variable and Voltage (V) as the constant variable.